Hospital development of heart failure follow-up units and short-term prognosis after acute decompensation in Spain. (1st May 2023) - López-Díez, María Pilar; Alquézar-Arbé, Aitor; Jacob, Javier; Llorens, Pere; Llauger, Lluís; Herrero, Pablo; Gil, Víctor; Núñez, Julio; Martín-Sánchez, Francisco Javier; Miró, Òscar; ,
Abstract: Objective: To investigate whether the existence of heart failure units (HFU) and link nurse units (LNU) in the hospital improve short-term outcomes of acute heart failure (AHF) episodes. Methods: Patients with AHF diagnosed in 45 Spanish emergency departments were analysed according to whether the hospital had a complete development of follow-up units (HFU + LNU), partial (HFU or LNU) or none. The outcomes were: 30-day mortality, hospitalization, in-hospital mortality, >7 days admission, and adverse event (death, rehospitalisation, or reconsultation to the emergency department) at 30 days post-discharge. Outcomes were adjusted for baseline and AHF episode characteristics. Results: 19, 947 patients were included, median age was 82 years (IQR 76‐–87), women were 55%. It was 20% of patients attended in hospitals with null development, 28% with partial development and 52% with complete development. Mortality at 30 days was 10.1% (null/partial/complete development: 10.5%/9.5%/10.4%; p =0.880), hospitalization 74.6% (72.7%/72.7%/75.7%; p <0.001), in-hospital mortality 7.4% (7.6%/7.0%/7.5%; p =0.995), prolonged hospitalization 47.4% (51.1%/52.4%/43.5%; p <0.001) and adverse events 30 days post-hospitalization 30.3% (36.2%/28.9%/30.3%; p < 0.001). In the adjusted analysis, hospital with complete development of follow-up units was not associated with mortality, but with increased hospitalization (OR= 1.172; 95%CI 1.069–1.285) and lower prolonged hospitalization (OR = 0.725; 95%CI 0.660–0.797) and adverse events at 30 days post-discharge (OR=0.831; 95%CI 0.755–0.916). Partial development was only associated with decreased post-discharge adverse events (OR= 0.782; 95%CI 0.702-0.871). Conclusion: The development of follow-up units is not associated with 30-day mortality, but is associated with less prolonged hospitalization and fewer post-discharge adverse events in patients with AHF. Highlights: Multidisciplinary approach of HF is essential to reduce readmission and improve survival. The follow-up units minimize hospital stay and avoid related adverse events. In patients with AHF attended in the ED, development of HF-units did not impact on mortality. It was found significant reduction of 30-day outcomes, mainly by a in HF decompensation.